Criminalization of HIV transmission and media coverage: crime news upholding sensationalism and homophobia - Carratalá, Adolfo (Revista Española de Comunicación en Salud, 2019)
Introduction: Current journalistic coverage of HIV mainly addresses the virus as a global epidemic, leaving out the risk-groups discourse that has linked the virus to the gay community. In recent years, HIV has been the subject of journalistic attention due to deliberate transmission of the virus being prosecuted. Objectives: This research analyzes the media coverage of two European men tried in 2017: Daryll Rowe, of Scotland, who was sentenced to life imprisonment for trying to infect 10 men with HIV, and Italian Valentino Talluto, convicted of transmitting the virus to 32 women. This study seeks to identify dominant characteristics of both coverages and the differences between the representations of the different sexual orientations of those involved. Methodology: Content analyses, both quantitative and qualitative, were applied to the 81 pieces of news coverage collected. Results: The coverage of the two trials privileges a sensationalist approach that upholds inaccuracies in the language used, and it is structured around the victim/villain dichotomy, showing differences between both episodes. Conclusion: Covering HIV as crime news promotes an emotional framing of the disease that can negatively affect how readers relate to HIV-positive people, in addition to revealing the persistence of certain homophobic biases in the media.
Keywords: HIV; media frame; sexual orientation; homophobia; sensationalism; stigma; victim; criminal prosecution